Theologies of the digital / [1] Theologies of the digital / herausgegeben von Hanna Reichel und Frederike van Oorschot - Reichel, Hanna; Oorschot, Frederike van (Theologies of the digital, 2022)
What, if anything, can theology contribute to the analysis, conceptualization and assessment of the emergent logics of "the digital"? And how are theological concepts and topics themselves transformed by "the digital"? In an interdisciplinary and constructive collaboration, this volume explores developments refract notions of the human, concepts of freedom, memory and knowledge, as well as understandings of scripture as authority and interface.